Cortical stimulation parameters for functional mapping. (February 2017) - Corley, Jacquelyn A.; Nazari, Pouya; Rossi, Vincent J.; Kim, Nora C.; Fogg, Louis F.; Hoeppner, Thomas J.; Stoub, Travis R.; Byrne, Richard W.
Highlights: No difference in stimulation threshold found between sensory and motor responses. There is a wide degree of variability seen among patients and thresholds. There are no predictive demographic factors for the thresholds of stimulation. Abstract: Purpose: There is significant variation in how patients respond to cortical electrical stimulation. It has been hypothesized that individual demographic and pathologic factors, such as age, sex, disease duration, and MRI findings, may explain this discrepancy. The purpose of our study is to identify specific patient characteristics and their effect on cortical stimulation, and discover the extent of variation in behavioral responses that exists among patients with epilepsy. Method: We retrospectively analyzed data from 92 patients with medically intractable epilepsy who had extra-operative cortical electrical stimulation. Mapping records were evaluated and information gathered about demographic data, as well as the thresholds of stimulation for motor, sensory, speech, and other responses; typical seizure behavior; and the induction of afterdischarges. Results: Ninety-two patient cortical stimulation mapping reports were analyzed. The average of the minimum thresholds for motor response was 4.15 mA ± 2.67. The average of the minimum thresholds for sensory response was 3.50 mA ± 2.15. The average of the minimum thresholds for speech response was 4.48 mA ± 2.42. The average of the minimum thresholds for afterdischarge was 4.33 mA ± 2.37. Most striking were the degree of variability and wide range of thresholds seen between patients and within the different regions of the same patient. Conclusion: Wide ranges of thresholds exist for the different responses between patients and within different regions of the same patient. With multivariate analysis in these series, no clinical or demographic factors predicted physiological response or afterdischarge threshold levels.